KEWENANGAN NOTARIS DALAM PENERAPAN DAN PENGEMBANGAN HUKUM EKONOMI ISLAM DI INDONESIA - Zham-Zham, Holly Muridi; Mataheru, Thea Yori (Jurnal Hukum Bisnis Bonum Commune, 2020)
The notary has an important role in the development of Islamic economics in Indonesia, where the notary has an extraordinary influence as well as in making an authentic deed that can produce legal certainty for the community. Law Number 30 of 2004 Juncto Law Number 2 of 2014 on the Position of Notary Public does not include the authority of a notary public in terms of making a deed of agreement relating to Islamic economics such as Islamic banking. The authority possessed by a notary in accordance with Law Number 30 of 2004 Juncto Law Number 2 of 2014 relating to the Notary is authorized to make an authentic deed regarding all deeds, agreements and stipulations required by legislation and / or as desired by the parties concerned to be stated in an authentic deed, guaranteeing the certainty of the deed, keep the deed, give a grosse, copy and quote the deed, all of it as long as the making of the Deed is not also assigned or excluded to other officials or other people determined by the law and other authorities. The regulation does not include notary authority in making notarial deeds related to sharia economics. Due to the development of the forms of agreements made by notaries, it is necessary to include a notary authority in making authentic deeds related to Islamic banking. Keywords : Notary, Islamic economics, Authentic deed.